2000
DOI: 10.1023/a:1013184613159
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Eighteen fungal species were isolated from rhizospheric soil and rhizoplane samples of three plant crops in southern Iraq. The fungal isolates were examined for the activities of four enzymes (amylase, cellulase, phenoloxidase, and protease), as well as their growth, against crude garlic extract added to the culture agar medium. A high reduction or inhibition of enzymatic activities was observed for the fungi treated with garlic extract compared with untreated fungal cultures. However, most of the species show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…We found a co-inoculation antagonistic relationship with a cucumber root pathogen (Fusarium infection) with the AM-inoculum + GS-substrate treatments, and the observed reduction, due to the strength of the applied dual inoculants responded with a more effective induction of rooting structure, increases in root activity, and thus, a pronounced influence on the fruit quality attributes (Table 6, Tables S2 and S3). The pragmatic bio-efficacy of this study could plausibly explain that garlic or garlic-derived potent compounds (flavonoids, sulfur-containing compounds, phenolic, carbohydrates, and antioxidants enzymes) have not only been recognized as bio stimulants [48,49,51] but have also been reported to be strong antimicrobial agents [52,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…We found a co-inoculation antagonistic relationship with a cucumber root pathogen (Fusarium infection) with the AM-inoculum + GS-substrate treatments, and the observed reduction, due to the strength of the applied dual inoculants responded with a more effective induction of rooting structure, increases in root activity, and thus, a pronounced influence on the fruit quality attributes (Table 6, Tables S2 and S3). The pragmatic bio-efficacy of this study could plausibly explain that garlic or garlic-derived potent compounds (flavonoids, sulfur-containing compounds, phenolic, carbohydrates, and antioxidants enzymes) have not only been recognized as bio stimulants [48,49,51] but have also been reported to be strong antimicrobial agents [52,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Most of fungi use various cell wall degrading enzymes to penetrate into the host cellular compartments (Tonukari, 2003) and if these enzymes are restrained or disrupted, the ability to penetrate into and consequently colonize inside host body is impaired. Muhsin et al (2001) reported that garlic bulb extracts significantly inhibited production of cell wall degrading enzymes in various fungi. A variety of organosulfur compounds such as DADS, DATS, Ajoenes etc., may contribute to the biological activity of garlic derived compounds (Avato et al, 2000; Rahman and Lowe, 2006; Yun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies that investigated antifungal activity of garlic against C. albicans ( Suleiman and Abdallah, 2014 ). High inhibition to fungi is attributed to the activity of allicin which is known to curb the performance of some enzymes that is important to fungal growth and activity ( Muhsin et al., 2001 ).…”
Section: Discussionmentioning
confidence: 99%